Implementation Of Policy For Poverty Reduction Program In Urban (P2KP) (Study In Kelambir Trade Village, Tanjung Morawa District, Deli Serdang Regency) - Muhammad Fadli Sinaga (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2020)
In theory, the implementation of the Urban Poverty Reduction Program Policy (P2KP) is one of the Government's programs in order to reduce the number of poor people. The Urban Poverty Reduction Program (P2KP) is hoped that the wider community will participate in thinking and seeking their potential so that they can jointly overcome poverty problems and care about social conditions in their living environment. The goal is to build an independent community that is able to establish togetherness and synergy with the government and local care groups in tackling poverty effectively and creating an orderly, healthy, productive and sustainable residential environment. Based on the results of data analysis on the Policy Implementation process of the Urban Poverty Reduction Program (P2KP) in Dagang Kelambir Village which is seen from the aspect of policy size and objectives, resources, communication, characteristics of implementers, disposition of implementors and social and environmental economy obtained using the method qualitative descriptive. As for the conclusions from the implementation of poverty reduction program policies, there are still many shortcomings, including the not optimal performance of the implementers involved in it. This is caused by several things, such as the data collection process that has not run optimally. For this reason, improvements are needed in the future, including increasing the capacity and understanding of the implementers themselves. This research is expected to be useful for readers and can also be input and consideration for relevant agencies in making policies or in making decisions.